Characterization of Immature Myofibroblasts of Stellate Cell or Mesenchymal Cell Origin in D-Galactosamine-Induced Liver Injury in Rats. Issue 1 (January 2021) - Rahman, Nahid; Kuramochi, Mizuki; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
Lesions of D-galactosamine (D-GalN)-induced hepatotoxicity resemble those of human acute viral hepatitis. This study investigated hepatic mesenchymal cells including hepatic stellate cells (HSCs) and myofibroblasts in D-GalN-induced hepatotoxicity. Rats, injected with D-GalN (800 mg/kg body weight, once, intraperitoneally) were examined on post single injection (PSI) at 8 hours and days 1 to 5. Lesions consisting of hepatocyte necrosis and reparative fibrosis were present diffusely or focally within the hepatic lobules on PSI days 1 and 2, and then the injury recovered on PSI days 3 and 5. Myofibroblasts expressing vimentin, desmin, and α-smooth muscle actin (α-SMA) were present in the lesions. Double immunofluorescence showed that myofibroblasts reacted simultaneously to vimentin/α-SMA, desmin/α-SMA, and desmin/vimentin; furthermore, myofibroblasts reacting to vimentin, desmin, and α-SMA also co-expressed glial fibrillary acidic protein (GFAP), a marker of HSCs. Additionally, GFAP-expressing myofibroblasts reacted to nestin and A3 (both are markers of immature mesenchymal cells). Cells reacting to Thy-1, a marker for immature mesenchymal cells, also appeared in fibrotic lesions. In agreement with the myofibroblastic appearance, mRNAs of fibrosis-related factors (TGF-β1, PDGF-β, TNF-α, Timp2, and Mmp2) increased mainly on PSI days 1 and 2. Myofibroblasts with expression of various cytoskeletal proteins were present in diffuse or focal hepatic lesions, and they might be derived partly from immature HSCs and from immature mesenchymal cells.